Anti-Inflammatory Chilean Endemic Plants - Martinez-Salinas, J; Morales-Munoz, B (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Medicinal plants have been used since prehistoric times and continue to treat several diseases as a fundamental part of the healing process. Inflammation is a condition characterized by redness, pain, and swelling. This process is a hard response by living tissue to any injury. Furthermore, inflammation is produced by various diseases such as rheumatic and immune-mediated conditions, cancer, cardiovascular diseases, obesity, and diabetes. Hence, anti-inflammatory-based treatments could emerge as a novel and exciting approach to treating these diseases. Medicinal plants and their secondary metabolites are known for their anti-inflammatory properties, and this review introduces various native Chilean plants whose anti-inflammatory effects have been evaluated in experimental studies. Fragaria chiloensis, Ugni molinae, Buddleja globosa, Aristotelia chilensis, Berberis microphylla, and Quillaja saponaria are some native species analyzed in this review. Since inflammation treatment is not a one-dimensional solution, this review seeks a multidimensional therapeutic approach to inflammation with plant extracts based on scientific and ancestral knowledge. © 2023 by the authors.